Highly selective and scalable CO2 to CO - Electrolysis using coral-nanostructured Ag catalysts in zero-gap configuration - Lee, Woong Hee; Ko, Young-Jin; Choi, Yongjun; Lee, Si Young; Choi, Chang Hyuck; Hwang, Yun Jeong; Min, Byoung Koun; Strasser, Peter; Oh, Hyung-Suk (ELSEVIER, 2020)
The direct electroreduction of CO2 to pure CO streams has attracted much attention for both academic research and industrial polymer synthesis development. Here, we explore catalytically very active, coral-structured Ag catalyst for the generation of pure CO from CO2-feeds in lab-bench scale zero-gap CO2 electrolyzer. Coral-shaped Ag electrodes achieved CO partial current densities of up to 312 mA cm(-2), EECO of 38%, and FECO clearly above 90%. In-situ/operando X-ray Absorption Spectroscopy revealed the sustained presence of Ag+ subsurface species, whose local electronic field effects constitute likely molecular origins of the favorable experimental kinetics and selectivity. In addition, we show how electrode flooding in zero-gap CO2 electrolyzer compromises efficient CO2 mass transfer. Our studies highlight the need for a concomitant consideration of factors related to intrinsic catalytic activity of the active phase, its porous structure and its hydrophilicity/phobicity to achieve a sustained high product yield in AEM zero-gap electrolyzer.